2020
DOI: 10.3389/fneur.2020.00249
|View full text |Cite
|
Sign up to set email alerts
|

Serum SNTF, a Surrogate Marker of Axonal Injury, Is Prognostic for Lasting Brain Dysfunction in Mild TBI Treated in the Emergency Department

Abstract: Mild traumatic brain injury (mTBI) causes persisting post-concussion syndrome for many patients without abnormalities on conventional neuroimaging. Currently, there is no method for identifying at-risk cases at an early stage for directing concussion management and treatment. SNTF is a calpain-derived N-terminal proteolytic fragment of spectrin (α II-spectrin1-1176) generated in damaged axons following mTBI. Preliminary human studies suggest that elevated blood SNTF on the day of mTBI correlates with white mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
0
8
0
3
Order By: Relevance
“…Calpain activation has long been shown to be involved in the pathology of traumatic brain injury (TBI) [ 84 , 85 , 86 ]. Calpain activation results in the truncation of brain spectrin and several spectrin breakdown products (SBDPs) have been used as biomarkers for TBI in both cerebro-spinal fluid (CSF) and blood [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Surprisingly, none of these studies has addressed the respective roles of calpain-1 and calpain-2 either in brain pathology or in the generation of the blood biomarkers.…”
Section: Calpain-2 Role In Neuronal Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Calpain activation has long been shown to be involved in the pathology of traumatic brain injury (TBI) [ 84 , 85 , 86 ]. Calpain activation results in the truncation of brain spectrin and several spectrin breakdown products (SBDPs) have been used as biomarkers for TBI in both cerebro-spinal fluid (CSF) and blood [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Surprisingly, none of these studies has addressed the respective roles of calpain-1 and calpain-2 either in brain pathology or in the generation of the blood biomarkers.…”
Section: Calpain-2 Role In Neuronal Deathmentioning
confidence: 99%
“…In good agreement with this result, the lesion volume 7 days after TBI was significantly smaller in C2CKO mice than in control mice ( Figure 4 ). Finally, we also determined the levels of calpain-cleaved αII-spectrin N-terminal fragment (SNTF), a blood biomarker shown to be present in human subjects after concussion [ 92 , 93 , 94 ], in the blood of mice subjected to TBI with or without treatment with a selective calpain-2 inhibitor ( Figure 5 ). First of all, we found that SNTF blood levels were very well correlated with the levels of calpain-2 activation in the brain; in addition, treatment of the mice with C2I 1 h after TBI prevented the increase in blood SNTF elicited by TBI.…”
Section: Calpain-2 Role In Neuronal Deathmentioning
confidence: 99%
“…Premorbid conditions have been shown to be associated with severity of PCS; where PCS is higher in those with a personal history of mood disorders ( 38 ). On the other hand, blood biomarkers have been modestly associated with mTBI ( 41 ) and used to predict long-lasting PCS ( 44 ). Hence, premorbid conditions, blood biomarkers, and imaging findings could be combined in a multimodal test to improve the assessment of severity and length of PCS using machine-learning approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SBDP as a potential biomarker in mild TBI in humans has been previously investigated [ 69 ]. Regarding its prognostic role in TAI, Siman et al [ 70 ] found that the serum levels of SNTF, a cleavage of αII-spectrin1-1176, could accurately predict long-term brain dysfunction in patients with long post-concussion syndrome, an entity strongly related to axonal injury. Indeed, it has been found that post-concussion syndrome is an entity with clinical, imaging, and histopathological correlation with axonal injury, with many authors reporting that concussion syndrome is in the milder spectrum of TAI [ 71 ].…”
Section: Biofluid Biomarkers Of Taimentioning
confidence: 99%